Conflict Resolution Education in Improving Learning Motivation for Junior high School - Harunnun Rasyid; Muchsin Muchsin; Hambali Hambali; Faudi Faudi (International Conference on Multidisciplinary Research, 2022)
Conflict resolution education is an effort to overcome problems faced by students, especially in increasing learning motivation. Students are inseparable from conflict. Both conflicts that occur from within the individual itself (personality) and conflicts that originate from outside the individual (interpersonal) such as conflicts between individuals and groups. Not all students have conflict resolution skills. Meanwhile, conflict resolution skills are very important for students to have to solve the problems faced in their lives in the future. Conflict resolution skills must be done are: able to orient, able to understand that each individual is different, able to see situations, empathize, and blame others, able to manage emotions, able to communicate well, able to think creatively in solving problems, able to think critically in predicting in analyzing conflicts. Keywords: Conflict Resolution Education, Learning Motivation